2017
DOI: 10.1103/physrevd.96.104028
|View full text |Cite
|
Sign up to set email alerts
|

Nonsingular black holes, wormholes, and de Sitter cores from anisotropic fluids

Abstract: We study Born-Infeld gravity coupled to an anisotropic fluid in a static, spherically symmetric background. The free function characterizing the fluid is selected on the following grounds: i) recovery of the Reissner-Nordström solution of GR at large distances, ii) fulfillment of classical energy conditions and iii) inclusion of models of nonlinear electrodynamics as particular examples. Four branches of solutions are obtained, depending on the signs of two parameters on the gravity and matter sectors. On each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 94 publications
3
46
0
Order By: Relevance
“…Regarding this, notice that these constraints arise from the perturbative effects of the non-metricity-induced corrections to GR that arise in generic RBGs. However, full non-perturbative solutions of some particular RBG models are known [43,51,82,96], and it would also be of interest to understand what is the non-perturbative counterpart of these non-metricity-induced interactions that arise in the matter fields from the perspective of the Einstein frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this, notice that these constraints arise from the perturbative effects of the non-metricity-induced corrections to GR that arise in generic RBGs. However, full non-perturbative solutions of some particular RBG models are known [43,51,82,96], and it would also be of interest to understand what is the non-perturbative counterpart of these non-metricity-induced interactions that arise in the matter fields from the perspective of the Einstein frame.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one of the original motivations to study gravitational theories within the metric-affine framework is that, even for higher-order curvature Lagrangians, the field equations for the metric are always second order, which could in principle alleviate the ghost problem, although it has been recently proved that this is not aways the case [39]. In the past fifteen years, the metric-affine framework has gained more attention due to some interesting results concerning the avoidance of space-time singularities in black-hole scenarios or in Big-Bang cosmologies even at a classical level and coupled to standard matter sources [40][41][42][43][44][45][46][47][48][49][50][51][52]. Given the fact that some approaches to quantum gravity present similar bouncing solutions, it has been suggested that metric-affine gravities could be understood as a low-energy limit of a possible quantum theory of gravity [19][20][21][22]53].…”
Section: Introductionmentioning
confidence: 99%
“…We would like to stress that the black hole solutions obtained in the mimetic Born-Infeld gravity here are still quite different from those obtained in the original EiBI gravity with matter. For example, in references [23,24] it was shown that by considering the standard Maxwell electromagnetic field or a static, spherically symmetric scalar field in the matter Lagrangian, the black hole singularity could be replaced with a wormhole, a nonsingular naked compact object, or a soliton-like solution, depending on the parameters involved.…”
Section: Conclusion and Further Discussionmentioning
confidence: 99%
“…The EiBI theory is able to cure the big bang singularity at the cosmological level [19]. Besides, some black hole singularities, once matter is included, are found to be altered [20][21][22][23][24]. However, the theory reduces exactly to GR in vacuum and the singularity predicted in a Schwarzschild black hole is still unavoidable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation